GAMIFICACIÓN Y SU INFLUENCIA EN EL APRENDIZAJE DE LOS ESTUDIANTES DE BACHILLERATO EN INFORMÁTICA DE LA UNIDAD EDUCATIVA 29 DE AGOSTO, PERIODO ACADÉMICO OCTUBRE 2023 - MARZO 2024 - MARTINEZ ARBELAI LADY GUADALUPE (2024)
The use of the gamification technique has made it possible to generate in students a commitment to learning in a fun way thanks to the motivation generated by using games in non-playful contexts, allowing them to develop skills and improve their academic performance, enriching their student competencies. This type of technique takes advantage of the natural predisposition that human beings have towards games and competitions, establishing a close relationship in dynamic and attractive activities, promoting intrinsic motivation. The general objective of this research is to determine the influence of gamification on the learning process of high school students in computer science at the August 29 educational unit. A descriptive level was used to help point out certain characteristics of the study. use of the mixed approach, which the qualitative method allowed us to obtain data necessary for the investigation and the quantitative approach for the collection of data from the respondents, the technique is documentary type because it allowed the collection of certified information and the data collection technique was The survey was based on 11 closed questions with the Likert scale aimed at students. With the data obtained, it was concluded that the use of the gamfication technique significantly influences the learning of the students of the 29 of August Educational Unit.